QBIDAN: Aplikasi Kebidanan Berbasis Mobile - Susilawati, Intan Rina; Satria, Eri; Rostilawati, Detila; Suryani, Naning; Ernawati, Ernawati; Handayani, Titi Purwitasari (Jurnal Algoritma, 2024)
Most midwife services still use manual recording, which is less effective, causing increased workload, difficulty finding information, and the risk of losing important data. This research aims to develop the QBidan application which provides various features to assist in monitoring pregnancy, provide health information, and offer useful resources and tips during the pregnancy journey. This application can also facilitate communication between pregnant women and health workers and provide guidance on nutrition, physical exercise, and preparation for childbirth. Research methods using waterfalls include communication, planning, modeling, construction, and implementation. The results of black-box testing and beta testing produced an average score of 4.8 (96%). The results of this evaluation show that the QBidan application that was built has met user needs. This research can be further developed by adding features such as a suburban calendar, consulting midwife services, and measuring technology acceptance by users.